2021
DOI: 10.1371/journal.pone.0246230
|View full text |Cite
|
Sign up to set email alerts
|

Late initiation of antenatal care and associated factors among pregnant women attending antenatal clinic of Ilu Ababor Zone, southwest Ethiopia: A cross-sectional study

Abstract: Timely entries to antenatal care have various benefits for pregnant women and birth outcomes. The aim of antenatal care is to assure that every pregnancy culminates in the delivery of a healthy baby without negative effects on the health of pregnant women through health promotion and disease prevention, early detection, and treatment of complications and existing diseases. Hence, this study assessed the late initiation of antenatal care and associated factors among pregnant women attending antenatal clinics at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
28
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 16 publications
8
28
3
1
Order By: Relevance
“…This is in line with reports made in 2013 from LMICs, 15 but is lower than the previous study in Ethiopia (38.8%). 37 Similarly, only 33.7% of study participants initiated ANC during the first trimester of pregnancy in Ethiopia. 17 The discrepancies of the results might be due to the previous facility-based studies’ which used a small sample size, varying definition of timely initiation of ANC visit (cut-of-point<12 vs <16 weeks), and other sociodemographic factors.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This is in line with reports made in 2013 from LMICs, 15 but is lower than the previous study in Ethiopia (38.8%). 37 Similarly, only 33.7% of study participants initiated ANC during the first trimester of pregnancy in Ethiopia. 17 The discrepancies of the results might be due to the previous facility-based studies’ which used a small sample size, varying definition of timely initiation of ANC visit (cut-of-point<12 vs <16 weeks), and other sociodemographic factors.…”
Section: Discussionmentioning
confidence: 96%
“…Timely initiation of ANC visits provides the opportunity to address pre-existing conditions on the appropriate time, perform a recommended test, and provide or get counselling. 48 It might also help women perceive the right time for the first ANC booking, 37 and be informed about its importance. 49 The low timely initiation of ANC may contribute to the low coverage of continuum of care, high maternal and neonatal morbidity, and high mortality in Ethiopia.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was determined using a single population proportion formula by considering the proportion of ANC late initiation, which is 71.2% in Ilu Ababora Zone, southwest Ethiopia, 95% significance level of Z α/2 = 1.96, 5% margin of error, and 10% of non-response rate ( 33 ).…”
Section: Methodsmentioning
confidence: 99%
“…26 Moreover, studies at the sub-national and national levels focused on timing and number of ANC visits rather than ANC content and associated factors. [27][28][29][30][31][32][33][34][35] Therefore, this study aimed to identify self-reported received ANC content and associated factors which may aid in designing guidelines and policies to improve maternal health, pregnancy outcomes, and child survival in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%